Unveiling protection: a meta-analysis of tixagevimab-cilgavimab prophylaxis in 28,950 transplant recipients and immunocompromised patients against COVID-19 - Mostafa Hossam El Din Moawad; Abdallah Abbas; Haneen Sabet; Mohamed Ahmed Zanaty; Abdullah Ashraf Hamad; Ayoub Rezkallah; Osama Ballut; Taha Fayad; Mona Mahmoud Elsakka; Francis Eshun; Hussien Ahmed H. Abdelgawad (Virology Journal)
Abstract Background This meta-analysis addresses the efficacy and safety of tixagevimab-cilgavimab as pre-exposure prophylaxis against COVID-19 in immunocompromised patients, particularly during the Omicron variant surge. Given the limited vaccine response in this population, alternative prophylactic strategies are critical. Methods Following PRISMA guidelines, we comprehensively searched electronic databases, including PubMed, Scopus, Web of Science, and Embase, up to June 22, 2024. We included studies assessing tixagevimab-cilgavimab's impact on SARS-CoV-2 infection rates, hospitalization, ICU admissions, and/or mortality among immunocompromised patients. Data synthesis and analysis were conducted using RevMan and Open-Meta Analyst software. Results Analyzing data from 36 studies involving 28,950 patients, tixagevimab-cilgavimab significantly reduced SARS-CoV-2 infection rates by 4.37%, hospitalization by 0.8%, and mortality by 0.5%. Compared to no prophylaxis, the drug combination showed a notable reduction in SARS-CoV-2 infection (OR = 0.33, 95% CI: 0.22–0.50), hospitalization (OR = 0.24, 95% CI: 0.15–0.39), and mortality (OR = 0.33, 95% CI: 0.16–0.66), exhibiting a favorable safety and efficacy profile. During the Omicron surge, tixagevimab-cilgavimab consistently reduced infection risk (OR = 0.32, 95% CI: 0.17–0.58). Conclusion Tixagevimab-cilgavimab offers a significant protective effect against COVID-19, including Omicron variants, in immunocompromised patients, underscoring its role as an effective pre-exposure prophylaxis. Future studies should further explore its efficacy across different SARS-CoV-2 variants and potential synergies with vaccination efforts.